Glyoxal in hyperglycaemic ischemic stroke - a cohort study - Rhein, Sina; Inderhees, Julica; Herrmann, Oliver; Othman, Alaa; Begemann, Kimberly; Fleming, Thomas; Nawroth, Peter Paul; Klika, Karel D.; Isa, Rakad; König, Inke R.; Royl, Georg; Schwaninger, Markus (Cardiovascular diabetology, 2023)
Hyperglycaemia is frequent in acute ischemic stroke and denotes a bad prognosis, even in the absence of pre-existing diabetes. However, in clinical trials treatment of elevated glucose levels with insulin did not improve stroke outcome, suggesting that collateral effects rather than hyperglycaemia itself aggravate ischemic brain damage. As reactive glucose metabolites, glyoxal and methylglyoxal are candidates for mediating the deleterious effects of hyperglycaemia in acute stroke.
Veröffentlicht: 12. Juli 2023
Gesehen am 22.08.2023